PRESTASI MAHASISWA DI NILAI DARI KONDISI EKONOMI KELUARGA DAN KOMPETENSI DOSEN - Seventeen, Winny Lian; yulianasari, nina (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to examine the effect of family economic conditions and lecturer competencies on student achievement in the economics and business faculty of Prof. University. Dr. Hazairin, SH. This research was conducted by the Faculty of Economics and Business, Prof. University. Dr. Hazairin, SH. The number of samples in this study were 93 respondents. The results showed that 24.1% of the variables of family economic conditions and the competence of lecturers were able to explain the variables of student learning achievement. Based on the results of the simultaneous test, the variables of family economic conditions and the competence of lecturers affect student learning achievement, while based on the partial test, the variables of family economic conditions affect student learning achievement and lecturer competencies affect student learning achievement.